An Overview of the Resilience of Nurses Exposed to Covid-19 - Jagentar Pane; Lindawati Tampubolon; Pricillia Zebua (GLOBAL HEALTH SCIENCE GROUP, 2022)
Resilience is a person's ability to adapt in stressful situations, be able to rise from the trauma experienced, and have a solution in solving every problem. Resilience is needed for nurses, as a foundation to always think positively in providing nursing care, especially during this covid-19 pandemic so that nurses have good sources of resilience. This study aims to describe the resilience of nurses exposed to COVID-19. The method used in this research is a descriptive research design with univariate data analysis. The sampling technique in this study is total sampling with a population of 89 nurses. The results show that the resilience of nurses exposed to COVID-19 at Bunda Thamrin General Hospital has a high category of resilience as many as 67 people (75.3%).